2017
DOI: 10.1016/j.trb.2016.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the issuance of evacuation orders under evolving hurricane conditions

Abstract: This paper develops a bi-level programming model to optimize the issuance of evacuation orders with explicit consideration of (i) the highly uncertain evolution of the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(16 citation statements)
references
References 78 publications
(88 reference statements)
0
16
0
Order By: Relevance
“…These findings indicated that the Government's information release mechanism before the arrival of a typhoon can play an important role in the evacuation process. Previous studies have shown that sending warnings judiciously (scientific information release mechanism) could help evacuation efficiency and reduce the cost of congestion in evacuation [45,46]. Thus, effective communication to people in hazardous areas in the process of evacuation can guide and promote the evacuation strategy of the evacuated groups.…”
Section: Impact On Cost Reduction In Evacuation Process Due To Governmentioning
confidence: 99%
“…These findings indicated that the Government's information release mechanism before the arrival of a typhoon can play an important role in the evacuation process. Previous studies have shown that sending warnings judiciously (scientific information release mechanism) could help evacuation efficiency and reduce the cost of congestion in evacuation [45,46]. Thus, effective communication to people in hazardous areas in the process of evacuation can guide and promote the evacuation strategy of the evacuated groups.…”
Section: Impact On Cost Reduction In Evacuation Process Due To Governmentioning
confidence: 99%
“…(5). Predicted changes in d t+k|t and C t+k|t over time are generally determined by evolving dynamics of routing environment [31], which is shown as follow:…”
Section: Mathematical Descriptionmentioning
confidence: 99%
“…Thanks to the booming computer science fields, many types of researches for natural disasters and short-term traffic flow forecasting spring up, which makes some changes become predictable more or less in routing environment, e.g., typhoons [30], [31], earthquakes and the spatial-temporal evolution prediction of traffic congestion [32]. However, the researches of path planning based on the dynamic prediction of routing environment emerge promptly.…”
Section: Introductionmentioning
confidence: 99%
“…In general, how to systematically assign disaster victims into road network is the main body of making an evacuation plan, which could directly influence the evacuation efficiency and even the social stability in the disaster-affected areas. The dynamic traffic assignment (DTA) models have been utilized as useful tools for making evacuation plans [ 4 8 ], the theories of which can be roughly summarized as analytical models and simulation models. However, there are some obvious disadvantages for those models More specifically, most of the analytical models cannot reflect traffic realities well and the model solutions are difficult to caculatewhen a large-size or even middle-size road network is considered [ 9 12 ].…”
Section: Introductionmentioning
confidence: 99%